Development and Testing of a Methodology for Assessing of the Correlation Velocity Measurements’ Accuracy for the Hydrodynamic Investigations of the Turbulent Coolant Flow in Nuclear Reactor Elements - I. A. Konovalov; A. A. Chesnokov; A. A. Barinov; S. M. Dmitriev; A. E. Khrobostov; M. A. Legchanov; S. S. Borodin; M. A. Makarov (Приборы и методы измерений, 2021)
The correlation method of the coolant flow measuring is widely used in research practice including for studying of turbulent coolant flows in scale models of elements of nuclear power plants. The aim of this work was to develop a technique for assessing the effect of noise recorded by a measuring system on the flow rate readings obtained using the correlation method.A technique to assess the effect of noise as well as the relative position and acquisition period of sensors is presented. An insignificant concentration of a salt solution (NaCl or Na2SO4 ) is used as a passive impurity which creates a conductivity gradient of the medium recorded by a conductometric system. Turbulent pulsations at the interface between two concurrent isokinetic flows in a channel with a square cross section are used as the signal source for the correlational algorithm.Paper presents the values of  the  turbulence′s  transport  time  between  spatial  conductometers, the results of estimating the spectral power density and band of the recorded signal and also the signalto-noise ratios of the measuring system obtained on their basis which are subsequently used to estimate the confidence interval of the transport time.As a result of measurements the relationship between the confidence  interval  value  and  the signal length were obtained. The measurements which were carried out at different relative positions of conductometers make it  possible  to  make  a  conclusion  about  an  increase  in  the  spectral  width of the signal and, as a consequence, a decrease in the length of the confidence interval with increasing of distance between sensors.The presented work is an approbation of this approach for its application as part of an experimental model of a nuclear reactor in order to determine per-channel flow rates in the channels of the core simulator using mesh conductometric sensors taking into account the effect of noise.